On the stability of capital structure of Nigerian quoted firms - Oluseun A. Paseda; Olusegun Felix Ayadi (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
One of the central debates in the empirical capital structure literature is the issue of capital structure stability. The purpose of this study is to examine the debate in the Nigerian context where it is largely an underexplored issue. This study employed the traditional leverage adjustment framework to examine the stability or adjustment of capital structure of a panel of Nigerian quoted firms in the presence of financing frictions. The population of this study comprised a panel of Nigerian quoted firms for the period 1999-2019 out of which 50 non-financial firms that met the data criteria were utilized as sample. Utilizing panel data generalized methods of moments (GMM) estimation techniques, the results revealed that capital structure variation overwhelms stability. The leverage measures exhibited strong sensitivities to firm-level variables, confirming trade-off, pecking order and market timing predictions. The target leverage was pro-cyclical in the sense of its sensitivity to macroeconomic variables. The study implications can be generalized to markets with similar characteristics, most notably that institutional rigidities exacerbate adjustment costs and, by extension, the gravitation of firms' debt dynamics towards slow adjustment.
Keywords: G30; G32; 330; Capital structure stability; financing frictions; target adjustment; trade-off; pecking order